Resistant Nonalcoholic Fatty Liver Disease Amelioration With Rosuvastatin and Pioglitazone Combination Therapy in a Patient With Metabolic Syndrome. (January 2014) - Riche, Daniel M.; Fleming, Joshua W.; Malinowski, Scott S.; Black, Catherine A.; Miller, Kristen H.; Wofford, Marion R.
Objective: To report a case describing resolution of persistently elevated aminotransferases in a patient with severe, resistant nonalcoholic fatty liver disease (NAFLD) using combination therapy.Case Summary: A 47-year-old obese male patient presented with a history of elevated aminotransferases and numerous statin intolerances. In addition to worsening control of diabetes and dyslipidemia, severe NAFLD was confirmed. Rosuvastatin was started, which induced short-term elevations in aminotransferases resulting in patient discontinuation. Biochemical markers of NAFLD worsened over time. Therefore, both rosuvastatin 20 mg daily and pioglitazone 15 mg daily were started simultaneously to potentially blunt the early increase in transaminases seen with rosuvastatin. At 2 weeks, the patient's alanine aminotransferase (ALT) and aspartate aminotransferase (AST) had decreased 57% and 56% from baseline, respectively. By 9 months, the patient's ALT and AST serum concentrations had normalized. Repeat liver ultrasound demonstrated improvement in steatosis grading and reduction in liver size. These improvements occurred despite a 4.5-kg weight gain since starting rosuvastatin and pioglitazone.Discussion: Pharmacotherapy in NAFLD is not well validated, particularly combination therapy. Medications that target obesity-related consequences are commonly used, although evidence regarding biochemical and histological improvement is inconclusive. Consideration should be given to the use of combination of thiazolidinediones and statins for rapid biochemical improvement and long-term histological impact.Conclusions: The improvement in this patient's biochemical and ultrasonographic markers of resistant, severe NAFLD was rapid and sustained with combination therapy. This case represents a potential solution for initiating or maintaining statin therapy in patients with NAFLD who are at high cardiovascular risk.